Penggunaan Layanan Aplikasi Pinjaman Kredit Online Ditinjau dari Perspektif Hukum Perjanjian - Kadek Anggik Dwiyanti; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Warmadewa Press, 2022)
This study aims to analyze and describe the validity of credit agreements through online applications and legal protection for injured parties in credit agreements through online applications. With the presence of fintech, it is caused by the transition from people's lifestyles that continue to develop. Online loan services are now starting to be widely discussed in the community. although with many acts of terror with unpleasant actions by using illegal online loans. In this case, the researcher uses normative or library methods, literature studies with secondary data such as laws, court decisions, and legal theories. With the results obtained in the study that the validity of the credit agreement cannot be separated from the validity of the agreement, namely in Article 1320 of the Civil Code through online applications, there are two types of protection for victims, where the first legal protection is preventive protection measures regulated in Article 29 POJK Number 77 /POJK.01/2016, while repressive protection for victims can file complaints and disputes can be resolved quickly. Complaints from users of Fintech services to platform organizers and immediately to take action.